Primary chondrosarcoma of breast - cytology with histopathological correlation: A rare case report with review of literature - Sankappa P. Sinhasan; K. V. Bharathi; Ramachandra V. Bhat; Simon David Dasiah (Wolters Kluwer Medknow Publications, 2014)
Malignant mesenchymal tumors of the breast other than angiosarcoma are extremely rare and comprise <0.5% of breast tumors. Primary chondrosarcoma of the breast is an extremely rare entity and only 10 cases are reported as single case reports in literature until date. A diagnosis of primary mammary sarcoma can be established only after excluding metaplastic carcinomas and malignant phyllodes by extensive sampling for evidence of in situ or invasive carcinoma. Here, we report a primary chondrosarcoma of breast in a 55-year-old lady diagnosed precisely on fine-needle aspiration cytology and confirmed by histopatholigcal examination after total mastectomy. We emphasize on diagnostic difficulties encountered in cytology smears and discuss differential diagnoses.